Mepacrine Labelling Test and Uranaffin Cytochemical Reaction in Human Megakaryocytes - Hourdillé, P; Fialon, P; Belloc, F; Boisseau, M R; Andrieu, J M (Thrombosis and Haemostasis, 1982)
5-HT storage organelles were observed by electron microscope analysis in human megakaryocytes. They were less numerous per unit of surface than in platelets. Their number depended on the visualization technique employed. Thus after fixation with calcium-enriched glutaraldehyde a higher number of very opaque organelles was observed than of uranaffin-positive organelles after the cytochemical uranaffin reaction. With conventional electron microscopy deep black granules characteristic of dense bodies were not observed.Fluorescent microscopy showed greenish-yellow granules distributed throughout the whole cytoplasm in 96 ± 1.4% of normal megacaryocytes incubated with mepacrine. In 85.6 ± 5%, 5.28 ± 1.28 granules per 10 ¼m2 were observed.With the mepacrine labelling test, 74% of the megakaryocytes of a patient with Hermansky-Pudlak syndrome contained no granules. A similar finding was made in the platelets of the same patient. This suggests that mepacrine also stains the dense bodies in the megakaryocytes and that in the Hermansky-Pudlak syndrome the platelet anomaly is secondary to a megakaryocyte anomaly.
Keywords: Megakaryocyte dense bodies; Hermansky-Pudlak syndrome; Mepacrine-labelling test